Psychological skills for mental toughness in handball players - Ana Isabel Lacárcel García; Verónica Tutte Vallarino; Cristina Reche García (Federación Extremeña de Balonmano; University of Extremadura, 2022)
The purpose of this study was to analyze the prevalence and relationship of resilience and optimism in a sample of 96 Spanish handball players (age M = 22.32; SD = 4.04) and to analyze the differences according to gender, sports category, age, level of competition and years of sports experience. The Wagnild and Young Resistance Scale (ER), 1993, was used to measure resilience and the Otero, Luengo, Romero, Gómez y Castro (1998) Spanish version of Life Orientation Test-Revised (LOT-R) for optimism. The results found indicate that most athletes have a moderate level of resilience (61.46%). Among the athletes, we find differences in the function of age and sports experience, being those over 21 years of age and those with more sporting experience, those with the highest levels of resilience. Most of athletes have a tendency to be optimistic (64.58%). The optimistic tendency is greater in those of senior category and in those who practice their sport for more than 5 years. Optimism appears positively related to resilience. Encouraging the optimism of our athletes could contribute to increasing their mental strength, their sports performance and their psychological well-being.